Shock compression of [001] single crystal silicon - Zhao, S. (2016)
Silicon is ubiquitous in our advanced technological society, yet our current understanding of change to its mechanical response at extreme pressures and strain-rates is far from complete. This is due to its brittleness, making recovery experiments difficult. High-power, short-duration, laser-driven, shock compression and recovery experiments on [001] silicon (using impedance-matched momentum traps) unveiled remarkable structural changes observed by transmission electron microscopy. As laser energy increases, corresponding to an increase in peak shock pressure, the following plastic responses are are observed: surface cleavage along {111} planes, dislocations and stacking faults; bands of amorphized material initially forming on crystallographic orientations consistent with dislocation slip; and coarse regions of amorphized material. Molecular dynamics simulations approach equivalent length and time scales to laser experiments and reveal the evolution of shock-induced partial dislocations and their crucial role in the preliminary stages of amorphization. Application of coupled hydrostatic and shear stresses produce amorphization below the hydrostatically determined critical melting pressure under dynamic shock compression.